A fast and sensitive method for detecting specific viral RNA in mammalian cells. - Paeratakul, U (1988)
A quick and sensitive method to quantitate viral RNA synthesis has been developed. Utilizing glutaraldehyde to fix infected cells onto nitrocellulose paper, viral RNA can be probed directly in situ. Viral message can be detected from as few as 10(4) infected cells. This technique can be used to study viral gene expression and can be adapted to screen the activity of antiviral agents such as interferon.